Neuromuscular electrical stimulation in critically ill patients in the intensive care unit: a systematic review - Ferreira, Lucas L.ima; Vanderlei, Luiz C.arlos Marques; Valenti, Vitor E.ngrácia (My University, 2014)
OBJECTIVE: To analyze the outcomes enabled by the neuromuscular electric stimulation in critically ill patients in intensive care unit assisted. METHODS: A systematic review of the literature by means of clinical trials published between 2002 and 2012 in the databases LILACS, SciELO, MEDLINE and PEDro using the descriptors intensive care unit, physical therapy, physiotherapy, electric stimulation and randomized controlled trials. RESULTS: We included four trials. The sample size varied between 8 to 33 individuals of both genders, with ages ranging between 52 and 79 years, undergoing invasive mechanical ventilation. Of the articles analyzed, three showed significant benefits of neuromuscular electrical stimulation in critically ill patients, such as improvement in peripheral muscle strength, exercise capacity, functionality, or loss of thickness of the muscle layer. CONCLUSION: The application of neuromuscular electrical stimulation promotes a beneficial response in critically patients in intensive care.